Class-Specific Histone Deacetylase Inhibitors Promote 11-Beta Hydroxysteroid Dehydrogenase Type 2 Expression in JEG-3 Cells - Katie L. Togher; Louise C. Kenny; Gerard W. O’Keeffe (International Journal of Cell Biology)
Exposure to maternal cortisol plays a crucial role in fetal organogenesis. However, fetal overexposure to cortisol has been linked to a range of short- and long-term adverse outcomes. Normally, this is prevented by the expression of an enzyme in the placenta called 11-beta hydroxysteroid dehydrogenase type 2 (11β-HSD2) which converts active cortisol to its inactive metabolite cortisone. Placental 11β-HSD2 is known to be reduced in a number of adverse pregnancy complications, possibly through an epigenetic mechanism. As a result, a number of pan-HDAC inhibitors have been examined for their ability to promote 11β-HSD2 expression. However, it is not known if the effects of pan-HDAC inhibition are a general phenomenon or if the effects are dependent upon a specific class of HDACs. Here, we examined the ability of pan- and class-specific HDAC inhibitors to regulate 11β-HSD2 expression in JEG3 cells. We find that pan-, class I, or class IIa HDAC inhibition promoted 11β-HSD2 expression and prevented cortisol or interleukin-1β-induced decrease in its expression. These results demonstrate that targeting a specific class of HDACs can promote 11β-HSD2 expression in JEG3 cells. This adds to the growing body of evidence suggesting that HDACs may be crucial in maintaining normal fetal development.